Clinical study of the management of scrotal swelling in adult patients at a rural medical college and research hospital - S., Kailashnath B.; Mohan, Ambikavathy; P., Akshatha A. (International Surgery Journal, 2022)
Background: Scrotal swellings are commonest clinical entities in surgical practice. Hydrocele is abnormal collection of serous fluid in the tunica vaginalis or any part of the processus vaginalis, which needs to be differentiated from other conditions and surgically managed. Methods: This prospective, observational study was carried out on 90 adult male patients between January 2021 to August 2021 diagnosed with scrotal swelling, admitted, treated at MVJMC and RH. Inclusion criteria were male patients of age >18 years. Exclusion criteria were patients with paediatric scrotal swellings. Routine blood investigations, COVID test and ultrasound of the scrotum was done. The patients underwent one of the standard surgical procedures and were observed for post-operative complications during their stay at the hospital and were followed up for 3 months. The collected data was analyzed using SPSS-21 software. Results: Collected data was analysed using SPSS-21. In our study hydrocele was seen in 48 (53.33%), epididymo-orchitis 5 (5.56%). 3 (3.33%) cases of varicocele, 2 (2.22%) cases of epididymal cyst and 1 (1.11%) each of sebaceous cyst, spermatocele, hematocele, sebaceous cyst, Fournier’s gangrene, infected encysted hydrocele, pyocele, scrotal abscess and filarial hydrocele. 2 (2.22%) testicular tumour and 21 (23.86%) testicular torsion. Of 90 patients 81 (90%) underwent surgery, while 9 (10%) patients were managed conservatively. Conclusions: Primary vaginal hydrocele was the commonest scrotal swelling. Ultrasound of the scrotum is diagnostic tool in differentiating from other swellings in the scrotum especially in testicular torsion when the testis can be saved. Jaboulay’s procedure was the commonest surgery performed with least complications.